SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAYANAN PENGIRIMAN BARANG MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Rudi Setiawan (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2023)
Delivery service is the distribution of goods from the manufacturer to the customer, but the service has a number of risks that may occur at the time of the delivery process, such as delayed delivery and damaged goods. For this, it is necessary to make the selection of the best delivery services by business operators so that customer satisfaction remains awake until the ordered product reaches the customer’s hands. To support this decision-making process, the Simple Additive Weighting (SAW) method is used by determining the weight value on each attribute and is continued with the best alternative weighing process that aims to help the public determine the choice of delivery services well and according to the desired criteria, the study uses 5 criteria namely tariffs, delivery speed, goods security, customer service and branch office distribution. There are 3 alternative goods delivery services assessed using the SAW method by 30 respondents who come from UMKM Tajurhalang with the highest ranking results available on JNE services.